2020
DOI: 10.1016/j.radonc.2020.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for overall survival of stage III non-small cell lung cancer patients on computed tomography: A systematic review and meta-analysis

Abstract: Introduction: Prognosis prediction is central in treatment decision making and quality of life for nonsmall cell lung cancer (NSCLC) patients. However, conventional computed tomography (CT) related prognostic factors may not apply to the challenging stage III NSCLC group. The aim of this systematic review was therefore to identify and evaluate CT-related prognostic factors for overall survival (OS) of stage III NSCLC. Methods: The Medline, Embase, and Cochrane electronic databases were searched. After study se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 84 publications
(485 reference statements)
1
24
0
Order By: Relevance
“…From a clinical point of view, it is not surprising that metabolically active tumor burden as measured by MTV turned out as the most relevant tumor-related quantitative PET/CT biomarker in our cohort. Similar observations have been reported for various disease stages of NSCLC, using PET/CT or conventional CT imaging for both the determination of baseline tumor burden and response to ICI [ 21 , 23 , 30 , 53 , 54 ]. Concerning first-line treatment using mono-ICI therapy, Dall’Olio et al recently reported an MTV ≥ 75 cm 3 as a biomarker of poor prognosis in a cohort of 34 pembrolizumab-treated NSCLC patients with PD-L1 expression ≥50%, with an OS of 4.7 M (0.3–9.1), while median OS was not reached in patients with MTV < 75 m 3 [ 22 ].…”
Section: Discussionsupporting
confidence: 80%
“…From a clinical point of view, it is not surprising that metabolically active tumor burden as measured by MTV turned out as the most relevant tumor-related quantitative PET/CT biomarker in our cohort. Similar observations have been reported for various disease stages of NSCLC, using PET/CT or conventional CT imaging for both the determination of baseline tumor burden and response to ICI [ 21 , 23 , 30 , 53 , 54 ]. Concerning first-line treatment using mono-ICI therapy, Dall’Olio et al recently reported an MTV ≥ 75 cm 3 as a biomarker of poor prognosis in a cohort of 34 pembrolizumab-treated NSCLC patients with PD-L1 expression ≥50%, with an OS of 4.7 M (0.3–9.1), while median OS was not reached in patients with MTV < 75 m 3 [ 22 ].…”
Section: Discussionsupporting
confidence: 80%
“…Finally, it is of great interest to report two meta-analyses recently published in the field of prognosis and lung cancer. The analysis by van Laar et al [57] concluded that the only factors affecting survival in stage III lung cancer are tumor-size and nodal-size related factors. Kothari et al [58], again, analyzed the prognostic value of the radiomics model in lung cancer and found significant heterogeneity among the studies (I 2 = 70.3%).…”
Section: Texture Analysis and Prognosis-focus On Lung Cancermentioning
confidence: 99%
“…Specifically, Van Laar [57] selected 11,996 results (including 519 duplicates) for his meta-analysis and after cross-reference searching, included a total of 65 publications, with 26 individual CT-related prognostic factors for OS of patients with stage III NSCLC described. The results show that tumor diameter is prognostic for patients with stage IIIB NSCLC.…”
Section: Texture Analysis and Prognosis-focus On Lung Cancermentioning
confidence: 99%
“…Cancer is one of the leading causes of all medical mortalities and one of the greatest medical challenges to date [ 1 , 2 ]. Human lungs are the most reported target sites for cancer development with a comparatively poor survival rate [ 1 ].…”
Section: Introductionmentioning
confidence: 99%